Exploring expert and patient opinions and recommendations regarding anti-retroviral treatment compliance - Frank, Janice Meryl (My University, 2007)
The recent introduction of antiretroviral treatment (ART) to the public health sector has meant that for millions of Human Immunodeficiency Virus (HIV)-positive patients this deadly disease has been transformed into a chronic condition. There has been much research done internationally on adherence to ART but in South Africa there has been little investigation in this area. This study aimed to bridge this gap by exploring expert and patient opinions and recommendatio ns regarding adherence to antiretroviral medication. To attain this, four experts and seven patients were interviewed using a semistructured interview schedule. The experts had worked within the HIV field for at least two years while the patients had been chosen from public antiretroviral roll-out programmes and had been on ART for at least six months. These interviews were audio recorded and transcribed. The transcriptions were then explored for themes using thematic content analysis. These themes were categorised and discussed under four broad categories: patients’ perceptions of barriers to adherence, patients’ recommendations for improving adherence, experts’ perceptions of barriers to adherence and experts’ recommendations for improving adherence.
Student Number : 9803027N - MA research report - School of Psychology - Faculty of Humanities
Keywords: HIV/AIDS; adherence; compliance antiretroviral medication